PHOTOCATALYTIC DEGRADATION OF FAST GREEN DYE IN AQUEOUS SOLUTION USING TITANIUM DIOXIDE AS PHOTOCATALYST - Reving Rashid; Akram Haji; Idrees S khalo (Science Journal of University of Zakho)
Research on the photocatalytic degradation of dyes and other organic pollutants become an interesting topic in the last two decades. Under UV irradiation, investigation and optimization of various experimental parameters were done for the photocatalytic degradation of fast green dye (FG) in the presence of titanium dioxide (TiO2) suspension. Initial dye concentration, photocatalyst dosage, and solution pH were the study parameters. Results showed that the rate at which FG dye degraded was accelerated by increasing the TiO2 dose. However, the degradation rate was adversely impacted by the rise in FG dye content from 3 to 9 mg/L. It was found that the highest percentage of color removal occurred when the pH of the medium was 6.5. FG was found to be degraded process reached equilibrium in 50 minutes using TiO2 photocatalyst, proving that it is an effective catalyst for the process. Additionally, the kinetics of FG dye degradation was studied, and it was followed by the pseudo first-order kinetics.